Synthesis of new bis-n-heterocyclic carbene complexes and their applications as potentiometric sensor for AG(I) and HG(II) ions / Nur Rahimah Said - Nur Rahimah, Said (2016)
A new series of bis-benzimidazolium salts namely, L1.Br, L2.Br, L3.Br, L1.PF6, L2.PF6 and L3.PF6 have been successfully synthesized and characterized by using fourier transform infrared (FT-IR), 1H and 13C nuclear magnetic resonance (NMR), and CHNS elemental analysis. The crystal structure of L1.Br and L1.PF6 were confirmed, by single crystal X-ray diffraction analysis. The selective complexation of synthesized bisbenzimidazolium salts were found by using conductometric method. L1.Br has been used to study the complexation process with Ni2+, Zn2+, Pd2+, Hg2+ and Ag+ metal ions in MeOH:H2O binary phases at different temperatures. The stoichiometric of the complexation reactions for Ni2+, Zn2+, and Pd2+ are 1:1 [M:L1.Br]. While, for Hg2+ and Ag+, two stoichiometries were obtained (2:1 [M:L1.Br] and 1:1 [M:L1.Br]). The stability constants (log ) obtained from GENPLOT software show that the values for Hg2+ and Ag+ ions are higher than the other metal ions. The thermodynamic parameters ( , , )    C C C G H S revealed that the complexations of L1.Br in all cases were found to be enthalpy destabilized but entropy stabilized. The negative value of calculated  C G is an evidence to prove the ability of the ligand to form stable complexes with metal cations and the process trends to proceed spontaneously. The experimental data was tested by using artificial neural network (ANN) program and was in a good agreement with the estimated data. The calculations based on density fuctional theory (DFT) were used to predict the metal binding capability of complexes. The combination of all the results revealed that the selective complexation of L1.Br is in the sequence of Ni2+<Pd2+<Zn2+<Hg2+<Ag+. Subsequently, new potentiometric self-plasticizing polypyrrole sensors based on L1.Br as ionophore were fabricated for determination of Hg2+ and Ag+ cation. The optimum membrane composition was obtained by using 89.4 wt.% monomer (pyrrole), 4.8 wt.% photoinitiator (DMPP), 0.2 wt.% lipophilic salt (NaTFB), and 5.6 wt.% ionophore (L1.Br). These sensors demonstrated good Nernstian responses of 28.10±0.29 mV/decade and 58.61±1.12 mV/decade with working ranges of 1.0×10-6-1.0×10-2 M and 2.5×10-6-1.0×10-1 M for Hg2+ and Ag+ cations, respectively. Both electrodes performed satisfactory over wide pH range and showed fast response time which was about 20 s with a good repeatability and reproducibility. The proposed electrodes can be used over a period of 30 (Hg-ISE) and 50 (Ag-ISE) days without showing any significant drift in working concentration range, slope and response time. It also had no significant interference in the performance of the fabricated Hg-ISE and Ag-ISE for determining Hg2+ and Ag+ cations. The proposed electrode was successfully used to determine various concentrations of Hg2+ and Ag+ cation in water and standard solution samples with satisfactory results. All data proved that the proposed Hg-ISE and Ag-ISE can be applied in determination of Hg2+ and Ag+ cations present in solution, respectively. The corresponding complexes of mercury(II) and silver(I) for all synthesized bis-benzimidazolium salts were prepared in order to understand the coordination of complexes formation. The bis-benzimidazolium salts were coordinated with Hg2+ and Ag+ metal cations through the carbene carbon, respectively which were proved by FT-IR and NMR data. The single crystal X-ray diffraction analysis data for L1.AgBr and L3.HgBr revealed that the coordination geometry of complexes is tetrahedral.